Establishing Initial Conditions in Support of Inflation Targeting - Zelmer, Mark (IMF Working Papers; Working Paper ;, 2002)
This paper provides some practical advice on establishing initial conditions in support of an inflation-targeting monetary framework. These conditions are divided into four areas: a mandate in support of an inflation objective and accountability for achieving this objective; macroeconomic stability; a sufficiently well-developed and stable financial system; and effective policy implementation tools. The measures taken by countries to meet these conditions are also reviewed.